INTRODUCTION OF ECONOMICAL PRODUCTION AS FACTOR OF INCREASE OF COMPETITIVENESS OF THE AIRCRAFT MANUFACTURING ENTERPRISE JSC «AVIASTAR-SP» - E. Muravyeva (Вестник университета, 2016)
The arguments proving need of introduction of economical production by the Russian enterprises for development of own competitive advantages are presented. Concepts of competitiveness of the enterprises at the heart of which the combination of the features made production and features of a production activity of the subject is used are considered. The most significant actions for introduction of economical production on JSC Avistar-JV are allocated. Communication of introduction of economical production by the Russian enterprises for increase of their competitiveness is tracked.